Construcionismo, práticas discursivas e possibilidades de pesquisa em psicologia social - MÉLLO, Ricardo Pimentel (2016)
This paper presents the constructionist movement as a critical perspective in Social Psychology, which proposes to understand and explain the processes of institutionalization that have made certain facts essentialized. For such, it focuses on the study of discursive practices, regarding language practice as a cause of effects. This language perspective makes research possible that focuses happenings in the interface between the uses of language and the conditions of its production and propagation. The movement indicates the need to redirect research to the regimes of truth that the discursive practices sustain or break and, also, for the relations of power that control, select and organize enunciations.